United Arab Emirates - Sonneborn, Liz. (New York : Children's Press, 2008)
An introduction to the United Arab Emirates, providing information on the history, geography, government, economy, people, religion, arts and sports, and everyday life in the Middle Eastern federation.
Then and now -- A varied land -- Desert life -- Emirati history -- A federation of Emirates -- A booming economy -- Natives and foreigners -- Faith in the Emirates -- Arts and sports -- Living day to day.
Includes bibliographical references (p. 134-135) and index.
7.8
5-8
Keywords: United Arab Emirates -- Juvenile literature; United Arab Emirates; United Arab Emirates; United Arab Emirates